2021
DOI: 10.1038/s41598-021-92014-4
|View full text |Cite|
|
Sign up to set email alerts
|

Machine learning algorithm improved automated droplet classification of ddPCR for detection of BRAF V600E in paraffin-embedded samples

Abstract: Somatic mutations in cancer driver genes can help diagnosis, prognosis and treatment decisions. Formalin-fixed paraffin-embedded (FFPE) specimen is the main source of DNA for somatic mutation detection. To overcome constraints of DNA isolated from FFPE, we compared pyrosequencing and ddPCR analysis for absolute quantification of BRAF V600E mutation in the DNA extracted from FFPE specimens and compared the results to the qualitative detection information obtained by Sanger Sequencing. Sanger sequencing was able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Thus, optimization of the ddPCR assay and strict quality control measures are needed to achieve accurate and reproducible results [ 58 , 62 ]. Improved artificial intelligence algorithms could also help towards this direction [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, optimization of the ddPCR assay and strict quality control measures are needed to achieve accurate and reproducible results [ 58 , 62 ]. Improved artificial intelligence algorithms could also help towards this direction [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance of target-containing droplets has also been used as label-free detection signals which, therefore, can trigger the sorting of droplets ( Figure 3 c). Limited to optical path length, the sensitivity of absorbance measurements can be improved by the elongation of the channel, extension of residence time, or integration of other techniques such as fluorescence-based and UV–vis spectra-based techniques [ 122 , 123 ] Future development may extend to full absorbance spectra and integrate analysis by artificial intelligence [ 124 , 125 ]. Due to the advances in cameras, processing hardware, and machine learning software with image processing algorithms, bright field images of droplets have been able to be real-time captured and processed into signals for droplet sorting ( Figure 3 d) [ 126 ].…”
Section: Detection Methodsmentioning
confidence: 99%
“…Colozza-Gama et al ( 19 ) previously compared Sanger sequencing and pyrosequencing for detecting a somatic driver mutation, and observed that pyrosequencing was vastly superior for the detection of single nucleotide variants, particularly in highly degraded tumor samples derived from formalin-fixed paraffin-embedded (FFPE) specimens. Using DNA samples isolated from FFPE specimens, all papillary thyroid microcarcinoma and lymph node metastases samples were screened for BRAF V600E mutation by pyrosequencing.…”
Section: Techniquesmentioning
confidence: 99%
“…In the era of next-generation sequencing (NGS) techniques, detection and analysis of the BRAF V600E mutation have been performed under clinical settings using a variety of different methods such as Sanger sequencing ( 18 ), pyrosequencing ( 19 ), reverse transcription-quantitative PCR (RT-qPCR) ( 20 ), amplification refractory mutation system (ARMS), NGS technology, high-resolution melting (HRM), droplet digital PCR (ddPCR) ( 21 ), MassArray ( 22 ) and immunohistochemistry (IHC)-based mutation detection ( 23 ). Among these methods, Sanger sequencing is considered to be the ‘gold standard’ in the majority of diagnostic studies.…”
Section: Introductionmentioning
confidence: 99%